Randomized, Double-Blind, Placebo-Controlled Study of Anti-Mycobacterial Therapy (RHB-104) in Active Crohn's Disease - David Y. Graham; Saleh A. Naser; Thomas Borody; Zbigniew Hebzda; Harry Sarles; Scott Levenson; Robert Hardi; Tomasz Arłukowicz; Petar Svorcan; Reza Fathi; Aida Bibliowicz; Patricia Anderson; et al. (MDPI AG, 2024)
This study, conducted between 4 October 2013, and 30 November 2018, tested the hypothesis that triple antimicrobial therapy, targeting Mycobacterium avium subspecies paratuberculosis (MAP), long considered a putative cause, would favorably affect Crohn's disease. A double-blind multicenter study of adults with active Crohn's disease, (i.e., Crohn's Disease Activity Index [CDAI] 220-450 plus C-reactive protein ≥ 1.0 mg/dL, fecal calprotectin (FCP) >162.9 µg/g stool, or recent endoscopic or radiographic confirmation of active disease) receiving concomitant standard-of-care Crohn's disease treatment (Clinicaltrials.gov: NCT01951326) were stratified by anti-tumor necrosis factor use and randomized (1:1) to anti-MAP RHB-104 (clarithromycin 95 mg, rifabutin 45 mg, and clofazimine 10 mg per capsule) (n = 166), resulting in clarithromycin 950 mg/day, rifabutin 450 mg/day, and clofazimine 100 mg/day, or placebo (n = 165) for up to 52 weeks. A greater proportion of RHB-104 versus placebo-treated patients met the primary endpoint-remission (i.e., CDAI < 150)-at week 26 (36.7% [61/166] vs. 22.4% [37/165], respectively; 95% CI for difference: 4.6, 24.0, p = 0.0048; chi-square test). Clinical response (reduction of CDAI by ≥100 points from baseline) at week 26 (first secondary endpoint) was also higher among the patients treated with RHB-104 (73/166 [44.0%]) compared with placebo (50/165 [30.3%]; 95% CI for difference: 3.4, 24.0, p = 0.0116), and it remained higher at week 52 among the patients treated with RHB-104 (59/166 [35.5%] vs. (35/165 [21.2%] for placebo; 95% CI for difference: 4.7, 23.9, p = 0.0042). A statistically significantly greater decline in FCP (another prospective efficacy endpoint) was also observed in RHB-104-treated patients, compared with placebo, at weeks 12, 26, and 52. The rates of serious adverse events were similar between groups (RHB-104: 18.7%; placebo: 18.8%). No patient died during the study. Antimicrobial therapy directed against MAP resulted in significantly greater improvement in clinical and laboratory (FCP) measures of active Crohn's disease.